2017
DOI: 10.1016/j.jfa.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Tiling sets and spectral sets over finite fields

Abstract: We study tiling and spectral sets in vector spaces over prime fields. The classical Fuglede conjecture in locally compact abelian groups says that a set is spectral if and only if it tiles by translation. This conjecture was disproved by T. Tao in Euclidean spaces of dimensions 5 and higher, using constructions over prime fields (in vector spaces over finite fields of prime order) and lifting them to the Euclidean setting. Over prime fields, when the dimension of the vector space is less than or equal to 2 it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…However, in [10] the authors showed that the Fuglede Conjecture holds in twodimensional vector spaces over prime fields. Then, in [2] the authors prove that tiling implies spectral in Z 3 p , p prime, and Fuglede conjecture is true for Z 3 2 and Z 3 3 . Very recently, important developments in LCA groups, with crucial implications on sampling theory, have been developed by E. Agora, J. Antezana and C. Cabrelli in [1], where the authors could obtain a full characterization of Riesz bases for multi-tiling sets in LCA groups.…”
Section: ) the System Of Translates { |ω|mentioning
confidence: 97%
“…However, in [10] the authors showed that the Fuglede Conjecture holds in twodimensional vector spaces over prime fields. Then, in [2] the authors prove that tiling implies spectral in Z 3 p , p prime, and Fuglede conjecture is true for Z 3 2 and Z 3 3 . Very recently, important developments in LCA groups, with crucial implications on sampling theory, have been developed by E. Agora, J. Antezana and C. Cabrelli in [1], where the authors could obtain a full characterization of Riesz bases for multi-tiling sets in LCA groups.…”
Section: ) the System Of Translates { |ω|mentioning
confidence: 97%
“…If A = 1 or p 3 , then A is a tile trivially. We suppose that 1 < A < p 3 By pigeon principle, we have (1,0)…”
Section: Spectral Sets ⇒ Tilesmentioning
confidence: 99%
“…Nevertheless, we either know few about for which group, the spectral set conjecture fails. We only know that the direction ‘Spectral sets Tiles’ fails on Z36 [15], Z83 [10], double-struckZp41emfalse(when p prime and p1mod4) and double-struckZp51emfalse(when p prime and p3mod4) [1]; the direction ‘Tiles Spectral sets ’ fails on false(double-struckZ/6double-struckZfalse)5 [12], (Z/6Z)3×double-struckZ6p, where p is prime with gcd(6,p)=1 [4] and false(double-struckZ/24double-struckZfalse)3 [5]. Actually, these non‐tile spectral sets (respectively, non‐spectral tiles) in finite abelian groups lead to non‐tile spectral sets (respectively, non‐spectral tiles) in euclidean spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could state a general Fuglede's conjecture for a locally compact Abelian group G, even for finite groups, and also called Fuglede's conjecture in G. In this general case, the generalized conjecture is far from being proved. For the works towards this general conjecture, we refer the readers to [4,5,6].…”
Section: Introductionmentioning
confidence: 99%